Diversity of Arthropod at Soybean (Glycine max l. Merr) With Different Planting Distances - Helda Orbani Rosa; Muhammad Indar Pramudi; Rinita Wulandari; As’ari As’ari (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
This study observed the spacing effect on arthropod diversity in soybean from November 2017 to January 2018. The treatments were arranged in a randomized block design, with five replications and five different spacings: A - 20x20 cm, B - 20x30 cm, C - 20x40 cm, D 20x50 cm, and E - 20x60 cm. The highest arthropods were found at the narrowest spacing (20x 20 cm) and the lowest at the broadest spacing (20x60 cm). Soybean plantations in the study area had a medium category for diversity index (H'), a fairly even category for evenness index (E), and a low category for dominance index (D). All types of relative index values did not differ between treatments.